Structural Properties of Zinc Oxide Powders prepared by Sol-Gel method - ام كلثوم القاضي و افطيمة الضبيع و المبروك الكرائني و نور الدين بوقيلة و كارلوس فاسكيز فاسكيز و مصطفى محمد عبدالله و عباس رحدر (Journal of Pure & Applied Sciences, 2019)
The zinc oxide (ZnO) nanopowders were prepared by the sol-gel method. The calcination process to calcine the samples was executed at different temperature values of 600° C and 700° C . The structures and morphology of samples were characterized using the X-ray diffractometer (XRD), Raman and the scanning electron microscope (SEM). An amorphous structure of as-prepared sample was confirmed by XRD patterns. The calcined samples at 600° C and 700° C exhibited the hexagonal (wurtzite) structure. The intensities of samples were increased with increasing of calcination temperature due to crystallinity improvement. The crystalline size values of the samples at 600° C and 700° C were 34 and 22 nm, respectively. At 700° C, the ZnO sample showed rods -like with the hexagonal shape. Also, Raman spectra indicate a sharp peak with high intensity located at 437 cm?1 related to E2 high mode due to well crystalline of the sample. Further measurements will execute for iodine doped ZnO powders to enhance their optical properties to be proper for the photocatalytic applications.